2018
DOI: 10.1016/j.chb.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Online celebrity aggression: A combination of low empathy and high moral disengagement? The relationship between empathy and moral disengagement and adolescents' online celebrity aggression

Abstract: Adolescents regularly become involved in online aggression. While existing research mainly concentrated on online peer aggression, some studies pointed to adolescents' aggression toward other targets, such as celebrities. It is known that socio-cognitive characteristics such as empathy and moral disengagement are associated with adolescents' aggression toward peers, but so far it remains unexplored if these traits can also explain celebrity aggression. The current study investigated the relationship between af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 72 publications
1
33
2
1
Order By: Relevance
“…Compared to the moral dimension, the potential invisibility of the victim might be a condition for a lack of empathy, which would not be activated. In the web scenario, the lack of direct contact (such as in face-to-face bullying and a normative social context-peer and adult), allows the subject to act immorally, without any perception of the suffering the victim might experience [9,44,45]. As previous studies have already shown, the mechanism of distorting consequences has been identified among the predictors of CB [27].…”
Section: Discussionmentioning
confidence: 90%
“…Compared to the moral dimension, the potential invisibility of the victim might be a condition for a lack of empathy, which would not be activated. In the web scenario, the lack of direct contact (such as in face-to-face bullying and a normative social context-peer and adult), allows the subject to act immorally, without any perception of the suffering the victim might experience [9,44,45]. As previous studies have already shown, the mechanism of distorting consequences has been identified among the predictors of CB [27].…”
Section: Discussionmentioning
confidence: 90%
“…The oxytocinergic system is known to regulate empathy and intranasal OT administrations were shown to enhance both affective empathy (Hurlemann et al 2010;Geng et al 2018) and cognitive empathy (Domes et al 2007;Shahrestani et al 2013). Therefore, based on the hypothesis that the perception of celebrity bashing is also grounded in human capacity for empathy (Ouvrein et al 2018a), we hypothesized that OT administration will decrease bystanders' acceptance of online celebrity bashing. A doubleblind, placebo-controlled experiment was performed to test this idea.…”
Section: Discussionmentioning
confidence: 99%
“…Having less empathy for the victim, on the other hand, increases the acceptance towards the behavior (Obermann 2011), which in turn reduces the motivation to support the victim (Thornberg et al 2012). Recently, Ouvrein et al 2018a demonstrated that empathy is also an important explaining variable for celebrity bashing. The authors found that lower selfreported empathy is a predictor of participation in severe types of online aggression towards celebrities.…”
Section: Empathy and Its Role In Explaining Celebrity Bashing Behaviormentioning
confidence: 99%
See 2 more Smart Citations